2019
DOI: 10.1093/gerona/gly270
|View full text |Cite
|
Sign up to set email alerts
|

Hereditary Hemochromatosis Associations with Frailty, Sarcopenia and Chronic Pain: Evidence from 200,975 Older UK Biobank Participants

Abstract: BackgroundIron is essential for life but contributes to oxidative damage. In Northern-European ancestry populations, HFE gene C282Y mutations are relatively common (0.3%–0.6% rare homozygote prevalence) and associated with excessive iron absorption, fatigue, diabetes, arthritis, and liver disease, especially in men. Iron excess can be prevented or treated but diagnosis is often delayed or missed. Data on sarcopenia, pain, and frailty are scarce.MethodsUsing 200,975 UK Biobank volunteers aged 60–70 years, we te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 31 publications
0
25
0
Order By: Relevance
“…Furthermore, using biobank PheWAS analysis, we verified known genetic pleiotropisms associated with cirrhosis promoting variants including dyslipidaemia, diabetes and body fat composition for six identified variants . Others have reported associations between HFE C282Y and arthritis, diabetes, chronic pain and brain iron accumulation, and SERPINA1 variants and hepatitis and fibrosis . Another recent study identified a SNP in MARC1 associated with cirrhosis, which was also associated with cirrhosis in UKBB ( P = .047); differences in strengths of associations are likely due to differences in statistical power and definitions of cirrhosis .…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, using biobank PheWAS analysis, we verified known genetic pleiotropisms associated with cirrhosis promoting variants including dyslipidaemia, diabetes and body fat composition for six identified variants . Others have reported associations between HFE C282Y and arthritis, diabetes, chronic pain and brain iron accumulation, and SERPINA1 variants and hepatitis and fibrosis . Another recent study identified a SNP in MARC1 associated with cirrhosis, which was also associated with cirrhosis in UKBB ( P = .047); differences in strengths of associations are likely due to differences in statistical power and definitions of cirrhosis .…”
Section: Discussionmentioning
confidence: 84%
“…However, there are also several possibilities by which the associations may be causal. Firstly, other studies highlight that adult grip strength and some long‐term conditions have common genetic factors . Secondly, arthritis such as at the wrist joint may lead to reduced grip strength.…”
Section: Discussionmentioning
confidence: 99%
“…Patients may present with more insidious symptoms including fatigue, mood disturbances and adynamia . A recent retrospective study of 1300 older patients with homozygous HFE C282Y gene mutations showed significant associations with chronic pain, frailty and sarcopenia .…”
Section: Clinical Manifestations Of Haemochromatosismentioning
confidence: 99%